EFEITO DA INOCULAÇÃO COM Azospirillum brasilense ASSOCIADO À REGULADORES VEGETAIS EM MILHO, UTILIZANDO DIFERENTES DOSES DE NITROGÊNIO - KLUGE, FABIÉLI TEIXEIRA DA ROSA (2016)
Corn is one of the cereals grown in the world, but it presents challenges in accurate fertilization. NO is an essential nutrient for development of maize, but is a nutrient that is easily lost by leaching, volatilization and denitrification-plant system requiring excessive applications, and as a result there is an increase in the cost of crop production and impacts negative to the environment. The diazotrophs can fix atmospheric nitrogen, which combined with bioregulators can produce substances that promote growth and may reduce the use of nitrogen fertilizer in corn. Thus, the present study is to assess the effectiveness of Azospirillum brasilense inoculation associated with plant growth regulator Stimulate® using different doses of nitrogen fertilization in corn. The experiment was conducted at the model farm, located in the municipality of Candói, PR. The corn sowing took place on October 12, 2013 using a hybrid AS1656. The experimental design was the sub-sub-split plot with compounds treatments of the combination of three forms of inoculation of A. brasilense (control, groove and seed treatment), five N rates (0, 75, 150, 225 and 300 kg ha-1), and the third factor was related to the use or not of plant growth regulator, constituting 30 treatments with four repetitions, totaling 120 experimental units. Each plot consisted of four rows (6.0 m length x 0,80 m lines). For the application of doses of A. brasilense was used 100 ml ha-1 via seed treatment, for inoculation in the groove were used 300 ml ha-1 applied directly in the planting furrow, and the control treatment without application. For the treatments with plant growth regulator, consisted of application of Stimulate® at a dose of 250 ml h-1. Evaluated the variables on the yield components (grain yield, thousand grain weight, damaged kernels, rows per ear, kernels per row and grains per spike) and crop characteristics (chlorophyll content, silking index, height plant and insertion of ear, senescent leaves in flowering, leaf nitrogen content, leaf area index, leaf content of macro- and micronutrients). With the results it is concluded that there was an increase in grain yield when inoculated with Azospirillum b. in seed treatment. ON positively influenced the variables, chlorophyll a, b and total leaf area index, ear insertion height, plant height, senescent leaves, number of grains per spike, number of kernels per row, thousand grain weight, leaf nitrogen and yield according to N levels applied. However the use of plant growth regulator Stimulate® does not provide answer regarding senescent leaves and leaf N content, and grain yield the results were positive only in association with the levels of nitrogen fertilization. For foliar macro and micro nutrients (P, K, S, Cu and Mn), these were influenced by treatments, except for Ca and Zn.